Fabrication of self-healing and hydrophilic coatings from liquid-like graphene@SiO2 hybrids. (18th November 2016) - Yang, Shiwen; Liu, Jiacheng; Pan, Fei; Yin, Xianze; Wang, Luoxin; Chen, Dongzhi; Zhou, Yingshan; Xiong, Chuanxi; Wang, Hua
Abstract: Functionalized liquid-like graphene@SiO2 hybrids are fabricated by using the graphene@SiO2 as core and nonionic copolymer as shell in aqueous solution at room temperature. The hybrid materials can flow above 45 °C and have a particular thermal invertibility. The morphology, chemical composition, dispersibility and stability, as well as rheological behavior are systematically characterized by various methods. It is shown that well-dispersed SiO2 nanoparticles are tightly anchored on the surface of graphene sheet via hydrogen bonding interaction under the synergetic effect of 3-(trimethoxysilyl)-1-propanethiol and copolymer to prevent the aggregation of graphene sheet. What is more, the hybrid materials keep remarkably stability and dispersibility in organic solvents and aqueous solution. More importantly, rheological tests indicate that viscoelastic behavior of graphene@SiO2 hybrids is effectively regulated through varying the amount of surface nonionic copolymer and silane coupling agent, respectively. In addition, the liquid-like graphene@SiO2 hybrids as a novel of hybrid coating make the substrates transfer from hydrophobicity to hydrophilicity. More interestingly, the damaged coating can be self-healed under immersing water or heating conditions, respectively. This simple and environment friendly approach will benefit for fabricating large scale graphene based hybrid materials in application of functional coating and rheological additives.